2022
DOI: 10.3389/fanim.2022.1051572
|View full text |Cite
|
Sign up to set email alerts
|

Commercial straight-deck trailer vibration and microclimate conditions during market-weight pig transport during summer

Abstract: The objective of this study was to collect and quantify three-axis acceleration data from six locations within commercial pig transport trailers during summer. Two trucks with straight-deck trailers transporting two loads per day were observed for 5 consecutive days (N = 20). Accelerometers were placed under the floor of each trailer’s top and bottom decks (DECs) in the center of three sections (SECs): fore, middle, and aft. Data from each trailer section were processed to calculate z- and x,y-axis root mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Previous studies reported that vehicle vibration can be considered an acute stressor causing physiological and behavior stress in animals [ 28 , 29 ]. Vibration exposure of pigs was compared with ISO thresholds for exposure action value (injury potential) of 8.5 m s –1.75 for VDV [ 8 ]. Also, VDV over 9.1 m s –1.75 has been considered as aggressive by the European Union [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that vehicle vibration can be considered an acute stressor causing physiological and behavior stress in animals [ 28 , 29 ]. Vibration exposure of pigs was compared with ISO thresholds for exposure action value (injury potential) of 8.5 m s –1.75 for VDV [ 8 ]. Also, VDV over 9.1 m s –1.75 has been considered as aggressive by the European Union [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor driving techniques such as sudden acceleration, braking and cornering affect the ability of animals to maintain stable posture [ 7 ]. The vibration caused by vehicle motion during transportation leads to a displacement in a pig’s center of gravity to be displaced in vertical, lateral, and horizontal directions resulting in discomfort and motion sickness for pigs [ 8 ]. A previous study showed that a good driving style is essential so that their bodies remain in the correct position with stress reduced to the minimum [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many transport factors might induce stress in animals, such as distance and duration, microclimatic conditions, trailer design (Schwartzkopf-Genswein et al, 2012) and stocking density (Warriss et al, 1998;Pilcher et al, 2011), as well as the location inside the trailer (Barton Gade et al, 1996;, mixing of unfamiliar animals at loading (De jong et al, 2000;Barton Gade, 2008a and2008b), microclimatic conditions inside the trailer (Driessen, et al, 2020) loading/unloading systems (Faucitano & Goumon, 2018), trailer vibration (Stephens et al, 1985;Gebresenbet et al, 2011;Alambarrio et al, 2022).…”
Section: Introductionmentioning
confidence: 99%